Scramble Fun Learning sebagai Inovasi Permainan Edukatif untuk Meningkatkan Literasi Membaca Siswa di SDN 1 Weet Kabupaten Maluku Barat Daya - Jems Sopacua; Titin Kempa; Rufiati Simal; Cristianti C. Kilikily (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
The low level of reading literacy in remote areas, such as the Muna Barat Daya Regency, poses a significant challenge in basic education. One innovation proposed to address this issue is the implementation of Scramble Fun Learning, an educational game-based approach designed to enhance reading literacy skills in students at SD Negeri 1Weet. This community service activity was carried out in two stages: a theoretical stage, which provided foundational understanding about the importance of literacy and gamification approaches, and a practical stage involving both teachers and fifth-grade students in word arrangement activities. Scramble Fun Learning combines game elements with a gamification approach by having students arrange words from random letters. The main objective is to train vocabulary recognition, strengthen reading comprehension, and increase student motivation to learn. In this activity, students are challenged to form words or sentences within a limited time, which not only stimulates their creativity but also makes the learning process more enjoyable and engaging. This method enables students to learn while playing, which is particularly effective in overcoming the boredom that often occurs in conventional learning. The results of this activity showed a significant improvement in student enthusiasm, active participation, and literacy skills. Many students who were previously disinterested in reading activities became more enthusiastic and motivated. Despite limitations in resources and time, the activity was still effectively implemented, thanks to creative adjustments made by the implementing team to ensure the material and activities were well received by both students and teachers. Overall, these findings indicate that Scramble Fun Learning is a highly potential and applicable approach to improving students' reading literacy, especially in areas with limited educational resources. This approach not only enhances literacy skills but also builds students' interest and motivation to continue learning.